Broadening participation in STEM : effective methods, practices, and programs - Wilson-Kennedy, Zayika; Byrd, Goldie S.; Kennedy, Eugene; Frierson, Henry T. (Emerald Publishing Limited, 2019)
U.S. students exit undergraduate science, technology, engineering, and mathematics programs at alarming rates. Less than 50 percent of the undergraduate students who enter STEM degree programs as aspiring freshmen complete degrees in these areas. This is especially true for minorities, whose departure from STEM degree programs is often twice the rate of others. Broadening Participation in STEM features chapters from developers of high impact educational practices and programs that have been effective at broadening the participation of underrepresented groups in the STEM disciplines. It explores strategies used with special populations of STEM aspirants including minority groups such as African Americans, Latino Americans, and Native Americans; persons from economically disadvantaged background; and persons with disabilities. This volume contributes to national knowledge of best practices in educating underrepresented students aspiring to STEM careers. This book provides campus-based faculty, administrators, and diversity professionals with a guide that can be used to develop programs designed to address specific student success and inclusion goals in STEM programs.
Includes index.
Keywords: Science -- Study and teaching (Higher) -- United States.; Engineering -- Study and teaching (Higher) -- United States.; Technology -- Study and teaching (Higher) -- United States.; Mathematics -- Study and teaching (Higher) -- United States.; Minority college students -- Recruiting -- United States.; Education -- Higher.; Education.; elektronické knihy; electronic books